A Review of Using Wearable Technology to Assess Team Functioning and Performance. (February 2023) - Hałgas, Elwira A.; van Eijndhoven, Kyana H. J.; Gevers, Josette M. P.; Wiltshire, Travis J.; M. Westerink, Joyce H. D.; Rispens, Sonja
Wearable technology enables collecting continuous in situ data from multiple people in various modalities, which can enhance team research and support, as the dynamic coupling of signals between interacting individuals (i.e., team coordination dynamics) is believed to reflect underlying processes and states of team functioning and performance. We conducted a systematic review on existing literature to evaluate the prospective use of wearable technology in research and practice. Using the IMOI framework as an organizing tool, our review revealed considerable support linking team coordination dynamics in different modalities to team functioning and performance, but also explicated the field's nascent status.